2022
DOI: 10.3389/fspor.2022.719063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerobic Training Progression on Blood Pressure in Individuals With Hypertension: A Systematic Review With Meta-Analysis and Meta-Regression

Abstract: IntroductionAerobic training of moderate intensity is the primary modality recommended in the management of hypertension. The manipulation of training variables can be an important strategy for the continuity of health benefits; however, little is known about the effects of the progression of aerobic training variables in the adaptations of blood pressure in hypertensive adults.ObjectiveTo analyze, through a systematic review with meta-analysis, the effects of aerobic training with and without progression on s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…In the present research, lower but non-significant resting systolic blood pressure (7.7 mm Hg) was reported during post-season testing. This hypotensive effect was found previous as post-exercise acute effect ( Carpio-Rivera et al, 2016 ) and after regular training interventions de ( de Barcelos et al, 2022 ). It could be caused by changes of blood volume, cardiac output and decreased total peripheral resistance ( Joyner and Limberg, 2014 ).…”
Section: Discussionsupporting
confidence: 75%
“…In the present research, lower but non-significant resting systolic blood pressure (7.7 mm Hg) was reported during post-season testing. This hypotensive effect was found previous as post-exercise acute effect ( Carpio-Rivera et al, 2016 ) and after regular training interventions de ( de Barcelos et al, 2022 ). It could be caused by changes of blood volume, cardiac output and decreased total peripheral resistance ( Joyner and Limberg, 2014 ).…”
Section: Discussionsupporting
confidence: 75%
“…With regard to blood pressure, a recent meta-analysis of data from 1207 hypertensive patients showed a significant reduction in systolic (−10 mmHg) and diastolic (−5.5 mmHg) blood pressure in subjects following aerobic training programs [ 23 ], with High-Intensity Interval Training (HIIT) also showing a significant reduction in older patients [ 24 ]; in addition, it has recently been shown that physical activity and exercise added to the usual care may further reduce BP in patients with resistant hypertension [ 25 ]; similar results have been observed in T2DM patients [ 26 ]. Similarly, strength training, by resulting in skeletal muscle hypertrophy, can lead to increased tissue responsiveness to insulin in terms of glucose storage and utilization.…”
Section: Cardiovascular Benefits Of Exercisementioning
confidence: 99%
“…The conclusion of this study is consistent with the published conclusion on the effect of aerobic training on blood pressure in patients with hypertension. The meta-analysis results of Cao et al [ 7 ], Igarashi et al [ 23 ], and de Barcelos et al [ 24 ] illustrated the reduction of SBP and DBP in the aerobic training group were about 8-12 mmHg and 5-6 mmHg, respectively. In this study, the WMD of the difference before and after the intervention was used as the effect quantity.…”
Section: Discussionmentioning
confidence: 99%